Transformasi Paradigmatik Ketahanan Nasional sebagai Kajian Stratejik - Ras, Abdul Rivai (UI Scholars Hub, 2018)
This article tries to elaborate national security in terms of science and an overview of the historically paradigmatic transformation. The study of national resilience in Indonesia has developed dynamically as a response to the development of strategic environment. Various approaches ranging from interdisciplinary to transdisciplinary are described as part of discovering the scholarly format of this study. This study is in its development into a universal approach and refers to the sciences related to the good governance, assessment of national strength and national security leadership. Also the study of national resilience is able to predict the potential of a nation's fall-wake or the failure of state administration to realize security and development. And the consequences of this study requires an interdisciplinary approach even trans-disciplinary.